RELATIONSHIP OF NURSE WORK EXPERIENCE AND EDUCATION WITH PATIENT HANDLING RESPONSE TIME IN INSTALLATION EMERGENCY ATTENTION RSUD dr. R. KOESMA TUBAN - Enggar, Adibah; Ilmiyah, Surotul; Sudrajad, Muhammad; Munir, Miftahul (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Response time can cause physical disability and death in patients, the speed, in this case, is an action less than 5 minutes from the patient's arrival at the Emergency department, indirectly experience and education may be related to the length of response time. Based on the problem above, the researcher is interested in researching The relationship between work experience and nurse education with response time for handling patients in the Emergency Installation of RSUD dr. R. Koesma Tuban. Method. This research uses an analytic survey research design with a cross-sectional time approach. Respondents in this study are all nurses at the RSUD Dr. R. Koesma Tuban were 23 nurses, the technique used in the study was total sampling. The independent variable in this study is work experience and nurse education while the dependent variable is the response time for patient care.The instrument used was a questionnaire, and the analysis of this study used the Pearson correlation test. Results & Analysis. Statistical test results on work experience variables with response time obtained Sig (2-tailed) of 0.04 less than 0.05 then there is a correlation, while for the education level variable obtained Sig (2-tailed) 0.58 greater than 0.05 then it does not have a correlation to response time. There is a relationship between work experience with the response time of handling patients and the level of education has no relationship with response time. Discussion.  Work experience had relationship with the response time of handling patients and nurses need to improve response time of handling patients.